Phonetic Teachers and the Reform Movement: evidence from records of the IPA. (2nd September 2021) - Ashby, Michael; Ashby, Patricia
ABSTRACT: This work attempts to discover something about the hundreds of relatively obscure language teachers around the world who put Reform Movement principles to work in their teaching. We use the surviving records of the teachers' memberships in the International Phonetic Association (IPA). At its foundation and for many years afterwards the IPA was primarily an association for language teachers, and the detailed membership lists which were regularly published in the Association's journal provide a historical resource of great value, especially when used in conjunction with a recently-produced index which facilitates rapid searching. An exploratory study which focuses on early members in Australasia reveals several forgotten figures who can be traced in other records and archives. The conclusion outlines the eventual transformation of the IPA's guiding principles and enquires into the effective lifespan of Reform Movement influence within the Association.